Development of CNTs-filled photopolymer for projection stereolithography. Issue 1 (16th January 2017) - Eng, Hengky; Maleksaeedi, Saeed; Yu, Suzhu; Choong, Yu Ying Clarrisa; Wiria, Florencia Edith; Kheng, Ruihua Eugene; Wei, Jun; Su, Pei-Chen; Tham, Huijun Phoebe
Abstract : Purpose: Polymeric parts produced by 3D stereolithography (SL) process have poorer mechanical properties as compared to their counterparts fabricated via conventional methods, such as injection or compression molding. Adding nanofillers in the photopolymer resin for SL could help improve mechanical properties. This study aims to achieve enhancement in mechanical properties of parts fabricated by SL, for functional applications, by using well-dispersed nanofillers in the photopolymers, together with suitable post-processing. Design/methodology/approach: Carbon nanotubes (CNTs) have high strength and Young's modulus, making them attractive nanofillers. However, dispersion of CNTs in photopolymer is a critical challenge, as they tend to agglomerate easily. Achieving good dispersion is crucial to improve the mechanical properties; thus, suitable dispersion mechanisms and processes are examined. Solvent exchange process was found to improve the dispersion of multiwalled carbon nanotubes in the photopolymer. The UV-absorbing nature of CNTs was also discovered to affect the curing properties. With suitable post processing, coupled with thermal curing, the mechanical properties of SL parts made from CNTs-filled resin improved significantly. Findings: With the addition of 0.25 wt.% CNTs into the photopolymer, tensile stress and elongation of the 3D printed parts increased by 70 and 46 per cent, respectively. With the significant improvement, the achieved tensile strength is comparable to parts manufactured by conventional methods. Practical implications: This allows functional parts to be manufactured using SL. Originality/value: In this paper, an improved procedure to incorporate CNTs into the photopolymer was developed. Furthermore, because of strong UV-absorption nature of CNTs, curing properties of photopolymer and SL parts with and without CNT fillers were studied. Optimized curing parameters were determined and additional post-processing step for thermal curing was discovered as an essential step in order to further enhance the mechanical properties of SL composite parts.